An evaluation of a training program conducted by a private training provider - Annamalai, Sathivalu (1998)
The purpose of this study was to evaluate a series of a training programs conducted by a private training provider from January 1996 to December 1997. The training program was 'Telephone Techniques and Courtesies' organized by a private training provider, Consembition Jaya Sdn. Bhd. located in Klang.Data collection was done by using secondary data derived from a questionnaire administered immediately after the completion of a session of a program. There were thirteen sessions of the program in all. A total of 249 participants responded to the questionnaire that was designed by The Human Resource Development Council, Ministry of Labour, Malaysia. The questionnaire typically sought the reaction of the participants in the areas of program content, program trainer, and general assessment, which many scholars would call a smile sheet or happiness indicator. This evaluation method was found to be the most popular method currently employed by most Human Resource practitioners, although many more reliable and effective tools are available.